Freeway traffic flow control by lumped parameter system approach - (:unkn) unknown (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2006)
Freeway traffic flows can be controlled by lumped parameter system approach owing to the space discretized system models. Such a control model incorporating a coordinated ramp metering mechanism is proposed in this study. The non-linear state equations representing the traffic system dynamics are derived from the conservation law in difference equations form. The control model is obtained by a feedback linearization approach, so that the target density of the controller is chosen as the critical density of the traffic system. Simulation based test studies have been done in a VISSIM simulation environment in order to compare the data obtained by the shock wave modified feedback linearization method to the non-modified type, with respect to the uncontrolled system performance. Test results show that the main-link flow performance is increased sufficiently by the proposed control model.
Keywords: WAVES